GRASSY-SHOOT MYCOPLASMA-FREE SUGARCANE PLANTLETS FROM APICAL MERISTEMS OF LATERAL BUDS - KISHAN SINGH, R. RAJ BHANSALI* AND (Indian Phytopathology, 2002)
Apical meristems of healthy and mycoplasma infected sugarcane plants (cv Co 1148) were grown on modified Murashige and skoog and White basal media. Shoot apices of healthy and infected buds elongated into leafy shoots within 30 days and formed root and root hairs when placed on the medium supplemented with NAA or IBA 5 mg/l. Approximately 30m per cent plantlets derived from infected bud apices were free from symptomi’ of grassy shoot disease of sugarcane. Number of disease-free plantlets increased upto 50 per cent when lower than 1.0 mm size of apices were used. Calli were developed. from. healthy Â and diseased bud apices on Murashige and Skoog medium supplemented with 2, 4-0 at 3.0 mg/l. Rate of callus growth was considerably slow in diseased callus than in healthy ones.